PENGARUH EDUKASI TERHADAP KEMAMPUAN KELUARGA DALAM PERAWATAN STOMA PADA PASIEN YANG MENGALAMI KOLOSTOMI DI RSUP. H. ADAM MALIK MEDAN TAHUN 2021 - Suriani Ginting (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The family can be involved in the patient's stoma care, so the family is expected to be able to monitor and help the patient to achieve self-care. Stoma is a bowel hole that appears on the surface of the abdomen in the reddish mucosa form. One way to increase family knowledge is by providing education. Education is an intervention that can help patients and families to maintain stoma health with appropriate care. The purpose of this study was to determine the effect of education on the ability of families on the treatment of stomas in patients undergoing colostomy at the General Hospital H. Adam Malik Medan. This research is a quantitative analytic study with a quasi-experimental research design by the pre and post test treatment groups. The population in this study were 71 people. A sample of 42 respondents representing the families of patients who had a colostomy at the General Hospital H. Adam Malik Medan. In this study, the analysis used is the Willcoxon Signed Rank Test, with p value <0.05. The average value of ability of the family before being educated was 2.00 and a range of 2 to 3. This shows that the ability of familieswas less in caring for stoma while the ability after being educated was of 3.00 and a range of 3 to 3. Its means that the family was able to perform stoma care for his family who had a colostomy. From the differences in the median value and probability was p <0.05. It can be concluded that education has an effect on increasing the ability of families in stoma care in patients undergoing colostomy.